A pilot intervention study to evaluate compliance to a peptide-based oral nutritional supplement in an adult population with impaired gastrointestinal function. (December 2019) - Nelson, Jeffrey L.
Summary: Background: Patients with gastrointestinal dysfunction have a reduced ability to digest and absorb nutrients and are often unable to tolerate oral nutritional supplements (ONS) containing whole protein. Peptide-based formulas have been shown to be more efficacious and better tolerated compared with whole protein formulas in malnourished patients. Compliance to ONS is essential to maximizing outcomes. We evaluated compliance to twice-daily use of a peptide-based ONS (220 mL Vital® 1.5, Abbott Nutrition, Columbus, Ohio, USA) in adult patients with chronic malabsorption or maldigestion, over a 16-day treatment period. Results: 25 evaluable participants (of 35 participants enrolled) were compliant to the study product for 97% of the 16-day treatment period, with the number of days compliant being 15.52, and the average daily percentage of the prescribed product consumed being 98.31%. A significant increase in mean body weight gain, mean body mass index and serum prealbumin of 0.90 Kg (p = 0.0035), 0.32 (p = 0.005) and 1.87 mg/dL respectively, was also observed. There were no significant changes in the total energy, protein, carbohydrate and fat intake from food alone before and during the study product intake. No safety concerns were observed. Conclusion: Oral supplementation with the peptide-based ONS (Vital® 1.5, Abbott Nutrition, Columbus, Ohio, USA) in adults with chronic malabsorption or maldigestion is safe and effective in improving nutritional status.